Prognosis of resectable colorectal liver metastases after surgery associated with pathological features of primary tumor - Chen, Dawei; Li, Qingshan; Yu, Haibo (Frontiers in Oncology, 2023)
Background: Surgery is an important means for patients with colorectal liver metastases (CRLM) to improve their long-term survival, and accurate screening of high-risk factors is crucial to guiding postoperative monitoring and treatment. With this in mind, the aim of this study was to investigate the expression levels and prognostic roles of Mismatch Repair (MMR), Ki67, and Lymphovascular invasion(LVI) in the tumor tissues of colorectal of CRLM. Methods: 85 Patients with CRLM who received surgical treatment for liver metastases after colorectal cancer resection from June, 2017 and Jan, 2020 were included in this study. Independent risk factors affecting the survival of patients with CRLM were investigated using a Cox regression model and the Kaplan-Meier method, and a nomogram for predicting the OS of patients with CRLM was established according to a Cox multivariate regression model. Calibration plots and Kaplan-Meier curves were used to assess the performance of the nomogram. Results: The median survival time was 39 months (95% CI: 32.05-45.950), and MMR, Ki67 and LVI were significantly correlated with prognosis. Multivariate analysis indicated that higher serum CA199 (HR = 2.275, 95%CI: 1.302-3.975 p=0.004), N1-2 stage(HR = 2.232, 95%CI: 1.239-4.020 p=0.008), the presence of LVI (HR = 1.793, 95%CI: 1.030-3.121 p=0.039), higher Ki67 (HR = 2.700, 95%CI: 1.388-5.253\ p=0.003), and pMMR (HR = 2.213, 95%CI: 1.181-4.993 p=0.046) all predicted worse OS. Finally, synchronous liver metastasis (HR = 2.059, 95%CI: 1.087-3.901 p=0.027), more than one liver metastases ((HR =2.025, 95%CI: 1.120-3.662 p=0.020),higher serum CA199 (HR =2.914, 95%CI: 1.497-5.674 p=0.002), present LVI (HR = 2.055, 95%CI: 1.183-4.299 p=0.001) , higher Ki67 (HR = 3.190, 95%CI: 1.648-6.175 p=0.001) and pMMR(HR = 1.676, 95%CI: 1.772-3.637 p=0.047) predicted worse DFS, and the nomogram achieved an effective level of predictive ability. Conclusion: This study showed that MMR, Ki67, and Lymphovascular invasion were independent risk factors for the postoperative survival of CRLM patients, and a nomogram model was constructed to predict the OS of these patients after liver metastasis surgery.